TECHNOLOGY OF TEACHING DEFINITE AND INDEFINITE INTEGRAL IN PROFESSIONAL TEACHING OF MATHEMATICS - Bakhodirovna, Kaxharova Saodat (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: In the article, taking into account the fact that it is becoming urgent to improve the quality of training of highly educated specialists in New Uzbekistan, a special state program was adopted in this regard. Method: Within the framework of the state program, conceptual approaches and directions to the problems of improving the quality of education are analyzed. Results: Conclusions and suggestions on improving the quality of education are recommended. Novelty: Taking into account the fact that it is becoming urgent to improve the quality of training of highly educated specialists in New Uzbekistan, a special state program was adopted in this regard.